Egyptian curse. 6 - "Blake, Chris" (London; HarperCollins Children's Books, 2014)
"On his sixth quest, Tom is in ancient Egypt, where he must fight alongside King Tutankhamun against an enemy invasion. Can he protect the king, survive the battle and find the final amulet?"--Publisher
Donated by "Book Planet", Dated 18-4-2025.
Keywords: Adventure stories